VARIASI MORFOLOGI DAUN JELUTUNG DARAT (DYERA COSTULATA) DAN JELUTUNG RAWA (DYERA POLYPHYLLA) - Arniana Anwar; Iskandar Z Siregar; Ulfah Juniati Siregar; Laswi Irmayanti; Reyna Ashari (Jurnal Pemuliaan Tanaman Hutan, 2022)
Jelutung is a tree species of the family Apocynaceae that is famous for its latex use as material for chewing gum. In Indonesia there are two species, namely jelutung land (Dyera costulata) and jelutung swamp (Dyera polyphylla). Until now, information on the differences in the two types of jelutung morphology is still very limited. There is therefore the need for a study on the variation of both types cultivated. This study was conducted to estimate variations in leaf morphology for land and swamp jelutung to assess 14 variables of its leaf morphology. Results of multivariate analysis (PCA, MCA, and CDA) showed that jelutung can be classified into two groups: D. costulata and D. polyphylla. PCA and MCA showed three variables that most distinguishes the two types of jelutung consecutive leaf length (PL), Roving Leaf (KL) and the shape of apex (AS). The CDA variables that play a major role in the classification of Dyera are the shape of apex (AS), the form of the base of the leaf (BS), leaf vein angle (SD).